Modelling of abrasive material loss at soil tillage via scratch test with the discrete element method. (October 2020) - Schramm, F.; Kalácska, Á.; Pfeiffer, V.; Sukumaran, J.; De Baets, P.; Frerichs, L.
Highlights: Discrete element method for investigating abrasive wear in soil tillage. Use of the Archard wear model. Geometric deformation via node shifting in automated co-simulation. Wear comparison between experimental scratch test and simulation. Abstract: The discrete element method (DEM) is one of the main modelling techniques in the agricultural sector to investigate soil tillage. There is a model-like description for material abrasion, which is often based on the determination of a virtual material removal, but the geometrical changes of the geometry, as well as the continuous load change upon the tool, are often not considered in the DEM simulations. Research on wear of tillage tools have been focused mostly on experimental studies with the result that abrasion is mainly caused by micro cutting on the contact surface. The single asperity scratch test is considered to be most suitable for evaluating materials due to its abrasive wear resistance. This paper presents an innovative approach that investigates the influence on the continuous wear process. The presented method describes the geometrical changes of the geometry based on the material loss. DEM simulations have replicated the single asperity test for different normal forces. Taking into account the geometric changes, these achieve the same wear volume and are therefore suitable for investigations of wear processes during soil tillage.